THE MATURITY LEVEL OF ENTERPRISE RISK MANAGEMENT IMPLEMENTATION IN MEDIUM-SIZED PRIORITY SECTOR COMPANIES IN EAST JAVA - Pwee Leng; Basuki Basuki; Rahmat Setiawan (International Journal of Financial and Investment Studies (IJFIS), 2022)
This study aims to measure the maturity level of Enterprise Risk Management in medium-sized priority sector companies in East Java. Studies on the application of ERM were previously focused more on big companies and tended to be carried out abroad and still gave inconsistent results. In addition, the number of studies on previous ERM that addressed the practice of its application on companies has not been that many. There are several studies on ERM conducted in Indonesia, however, the research objective focuses on the financial services industry referring to large companies listed on the Indonesia Stock Exchange. Although several studies have yielded significant results for application in medium-sized companies, they are only centered on construction services companies. There are 16 indicators used to measure the maturity level of ERM implementation in this study that have been adjusted to the characteristics of medium-sized industrial companies in Indonesia. The results of this study indicate that all medium-sized industrial companies in East Java have implemented integrated risk management (ERM) and have reached the optimal maturity level in implementing ERM. The results of the study also found that the automotive and electronics industry sectors are 2 industrial sectors that have the highest level of maturity in implementing ERM. Meanwhile, the lowest maturity level occurred in the food and beverage industry sector.